EFFECT OF LEUCAENA LEUCOCEPHALA LEAFY BIOMASS AND NPK FERTILISER ON THE GROWTH AND YIELD OF OKRA, ABELMOSCHUS ESCULENTUS (L.) MOENCH - Adams Latif MOHAMMED; Kaddiri Nanbaala Kumodu NASIM; Ali MORO (Journal of Applied Life Sciences and Environment)
Okra, Abelmoschus esculentus (L.) Moench, is a multipurpose vegetable crop grown in tropical and subtropical regions of the world for its immature seed pods and leaves. The crop seldom reaches its yield potential in most of these areas, primarily due to a decline in soil fertility. As a result, a field experiment was carried out at the Faculty of Renewable Natural Resources Demonstration Farm, KNUST-Kumasi to assess the effect of NPK (15:15:15) fertiliser and Leucaena leucocephala leafy biomass application on the growth and yield of okra. The treatment combinations were laid out in a 3 × 3 factorial randomised complete block design with 9 treatments replicated 4 times for a total of 36 experimental units. Leucaena leafy biomass and NPK were evaluated solely and in combinations at a rate of 75 kgN/ha on a weight basis. The treatment combinations were applied as follows: T1 = Control; T2 = 0.14 kg NPK (15:15:15); T3 = 0.07 kg NPK (15:15:15); T4 = 0.5 kg L. leucocephala leafy biomass; T5 = 0.25 kg L. leucocephala leafy biomass; T6 = T2 + T4; T7 = T3 + T5; T8 = T2 + T5; T9 = T3 + T4. The number of days from planting to the first anthesis of okra differed significantly (p ˂ 0.05). T3 showed the least number of days to the first anthesis observation (47 days), while T9 had the highest number of days to the first anthesis (49.3 days). On a weekly basis (starting with 5 weeks after planting, WAP), height was not significantly different among the various treatments. Stem diameter followed a sequence similar to plant height, starting from 5 to 10 WAP, where no significant differences occurred between treatment means. However, mean values revealed that okra plants varied significantly in height; T9 had the tallest plants (27.2 cm), while T2 and T8 had the shortest plants (21.2 and 21.2 cm, respectively). There was a significant difference between the treatment means and stem diameter. In the same advanced line, T9 had the highest stem diameter (9.9 mm), with T5 having the lowest stem diameter (6.9 mm). Fruit yield was also significantly different, with T4 having the most fruit (39,259 fruits per ha) and T8 having the least (19,259 fruits per ha). The fruit dry weight was significantly different, as the highest weight was recorded in T7 (12.5 tonnes/ha) and the lowest was recorded in T9 (5.3 tonnes/ha). The combination treatment T9 [0.07 kg NPK (15:15:15) fertiliser + 0.5 kg L. leucocephala leafy biomass per plot] had a significantly improved height and diameter compared to the other treatments. The highest fruit yield of okra was recorded in T4 (0.5 kg L. leucocephala leafy biomass per plot), and the highest dry weight of okra was registered in T7 (0.07 kg NPK (15:15:15) fertiliser + 0.25 kg L. leucocephala leafy biomass per plot). Therefore, it is recommended that sole L. leucocephala leafy biomass (T4) and its combination with NPK (15:15:15) fertiliser (T9) be adopted by smallholder farmers to cultivate okra in the tropics.